Empathy in the time of ecological apartheid : a social sculpture practice-led inquiry into developing pedagogies for ecological citizenship - McGarry, Dylan Kenneth (Rhodes University, Faculty of Education, Department of Education, 2014)
Considering the ecological crisis and the increased disconnection between human beings and nature, this study attempts to find the social and aesthetic educational response needed for developing ecological citizenship for the 21st century. In this transdisciplinary study I articulate what at first seems a clumsy attempt to enable the capacities of the embodied ecological citizen, and which later emerges as an alchemical 'social sculpture' approach to learning that expands the range of capacities available to the citizen and the citizen's immediate community. This learning bridges the gap between purely biocentric and technocentric forms of education, and addresses the ambiguity of concepts and forms of action such as 'sustainability'. My primary focus is enabling both communal and personal forms of agency: new ways of 'doing' and 'being' in the world as it changes radically. I argue that this demands constantly reflecting on and engaging without understanding, place and perception of the problems we see. Attending to a call for the importance of complex learning processes, that deepens our understanding of sustainability, and the need for methodological and pedagogical approaches to accessible forms of learning socially in the era of climate change and environmental degradation, this study offers a particular insight into the education of an ecological citizen. In particular I examine a form of learning that enables individuals to explore relationships between themselves and their ecologies (both physical and social), and that encourages personal forms of knowing so that each person's values can be cultivated within the experience and intuitive expression from both inner and outer realities. Central to my research focus is addressing the difficulties inherent in 'ecological apartheid', which is defined as a growing separation of relationships that include the human being's relationship with the natural world, as well as disconnections experienced within one's own inner and outer capacities. Subsequently I investigate forms of learning that encourage agency that most appropriately enable citizens to respond personally to both inner and outer forms of disconnection. 'Personal' and 'relational agency' are defined and investigated through an initial twelve-month collaborative participatory contextual profiling exploratory research period in South Africa (phase A), where I explore various forms of multiple-genre creative social learning practice that develop an accessible set of methodologies and pedagogies for the ecological citizen. Through this exploratory research, I place significance in the relatively unknown field of social sculpture, which I investigate through a self-made apprenticeship with Shelley Sacks, an expert in the field. This is documented through a rigorous ethnographic inquiry over a period of 18 months. Following this I undertake another two-year collaborative, practice-based research study across South Africa (phase B: 17 towns, with a total of 350 citizens) and eventually abroad (United Kingdom, Germany, USA and Belgium).The focus of this study was the implementation of a collaboratively developed citizen learning practice entitled Earth Forum developed by Shelley Sacks as a progression from her work "Exchange Values: voices of insivible lives" and my collaboative exploration into Earth Forum and its further development draws heavily from social sculpture methods obtained during the apprenticeship, and applied in 36 different incidences. I further explore the efficacy of this practice in enabling and expanding the capacities of participants, particularly those that encourage the development of personal and relational agency. This was achieved through a pedagogical development and expansion period (phase C). A primary finding through the iterative phase (phase D) was the value of imaginal contemplation, attentive listening, and empathy as capacities that enable an ecological citizen's overall capability. I ascribed this to Nussbaum and Sen's (1993) capability theory and the need to enable the articulation and implementation of a citizen's valued 'beings and doings'. Through this iterative phase, specific attention is given to listening and intuitive capacities in enabling personal and relational agency, and specifically I observed the fundamental role of imagination in this form of learning. Particularly valuable for the educational contribution of this study is the pedagogical development of the Earth Forum practice that enables an accessible, socially constructed form of learning. This contributes specifically to exploring 'how' social learning is undertaken, and I argue that an aesthetic approach to learning is vital for the education of the ecological citizen. I carefully describe how one can conduct collaborative practice-based research that utilises creative connective practice in agency development. This collaborative approach, with regard to learning socially and capacity development for ecological citizenship (that focuses its attention on addressing ecological apartheid and separateness), is articulated through a multiple-genred text. I found that empathetic capacity in ecological citizen education is relatively unexplored, and within listening and as well in empathy theory, that the role of imagination in listening and empathy development, requires greater attention. I attempt to reveal how connective practice considers aesthetic form and shape in expanding capacities of human beings, and introduce novel expanded forms of developing pedagogies that encourage personal and relational agency in the context of ecological apartheid from the artsbased field of social sculpture. Finally, I aim in this study to share the potential value found in social sculpture theory and practice into the field of environmental education and social learning through a reflection on the current context of education and social learning, and its potential enrichment via social sculpture processes.
Keywords: Education -- Philosophy; Social learning; Environmental education; Arts in education